2009
DOI: 10.2202/2161-2412.1053
|View full text |Cite
|
Sign up to set email alerts
|

The Misrepresentation of Culturally and Linguistically Diverse Students in Special Education

Abstract: Young, Wright, and Laster (2005) stated that since the Brown v. Board of Topeka, Kansas decision, gaps in educational achievement have been a recognized problem across the United States. Particularly, differences in achievement levels for elementary and secondary African American students have remained. Daniels (1998) stated that students who are culturally and linguistically diverse have always been challenged with inequality in our system of education. This article examines the critical issues resulting in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…It is suggested that cultural variance contributes to stereotyping and discounts the values and norms of a given culture. Educators must consider their own cultural background and experiences (Allday, Duhom, BlackburnEllis, & Van Dycke, 2011;Fitts & Gross, 2012;Grant & Barger-Anderson, 2009) and the extent to which it impacts their views about individuals from other cultures. Determining how a primary culture impacts attitude, behavior, and communication provides a first step to understand key differences between the majority culture of a school and underrepresented populations.…”
Section: Establishing a Sense Of Culturementioning
confidence: 99%
“…It is suggested that cultural variance contributes to stereotyping and discounts the values and norms of a given culture. Educators must consider their own cultural background and experiences (Allday, Duhom, BlackburnEllis, & Van Dycke, 2011;Fitts & Gross, 2012;Grant & Barger-Anderson, 2009) and the extent to which it impacts their views about individuals from other cultures. Determining how a primary culture impacts attitude, behavior, and communication provides a first step to understand key differences between the majority culture of a school and underrepresented populations.…”
Section: Establishing a Sense Of Culturementioning
confidence: 99%
“…Culturally and linguistically diverse (CLD) students are significantly overrepresented in special education and are unnecessarily and inappropriately referred for special education services by teachers who lack cultural competence, conflate diversity with disability (Ferri & Connor, 2005;Grant & Barger-Anderson, 2009;Anastasiou & Kauffman, 2012;Winzer & Mazurak, 2017), racialize disability, and who have implicit biases that affect the referral decision (Artiles, 2013;Seidl & Pugach, 2009;Sleeter, 2008;Sleeter, 2017). As a result, students without disabilities are wrongfully removed from the general education setting, leading to limited access to the general education curriculum.…”
Section: Chapter Ii: Review Of the Literaturementioning
confidence: 99%